The Online Media Representation of Bullying Issue: A Case of Audrey - Ghina Aulia Saffanah (Universitas Pendidikan Indonesia (UPI), 2021)
This study analyzed the online media representation of Audrey’s bullying issue by identifying the appraisal devices used in reporting the case of Audrey in five news portals. The study aimed to reveal the reporting strategy by exploring the appraisal devices and identifying the potential representational meanings. The data included five news related to Audrey’s Bullying in 2019, analyzed by grouping the clauses to mark engagement, attitude, and graduation used in language according to Martin and White’s (2005) Appraisal System. The appraisal analysis shows that all of the five news portals dominantly used Engagement (Monogloss-Heterogloss) and Attitude (Judgement) to construct their news discourse. The five news portals also show a rather similar negative-reaction to the issue. However, the use of the appraisal devices of these five news portals varied in accordance with the context and the main focus of the news, contributing to the news’ representation which covers specific perspective, generalization, and victimization.